Alkane production from biomass: chemo-, bio- and integrated catalytic approaches. (December 2015) - Deneyer, Aron; Renders, Tom; Van Aelst, Joost; Van den Bosch, Sander; Gabriëls, Dries; Sels, Bert F
Graphical abstract: Highlights: Renewable alkanes for fuels, chemicals and materials: a perspective. Chemo- and biocatalytic tool box to convert biomass into alkanes. Focus on the mild and selective chemocatalytic approach. A plot, inspired by van Krevelen, gives similarities between biomass and alkanes. The next step: improve current technology and multidisciplinary collaboration. Abstract : Linear, branched and cyclic alkanes are important intermediates and end products of the chemical industry and are nowadays mainly obtained from fossil resources. In search for alternatives, biomass feedstocks are often presented as a renewable carbon source for the production of fuels, chemicals and materials. However, providing a complete market for all these applications seems unrealistic due to both financial and logistic issues. Despite the very large scale of current alkane-based fuel applications, biomass definitely has the potential to offer a partial solution to the fuel business. For the smaller market of chemicals and materials, a transition to biomass as main carbon source is more realistic and even probably unavoidable in the long term. The appropriate use and further development of integrated chemo- and biotechnological (catalytic) process strategies will be crucial to successfully accomplish this petro-to-bio feedstock transition. Furthermore, a selection of the most promising technologies from the available chemo- and biocatalytic tool box is presented. New opportunities will certainly arise when multidisciplinary approaches are further explored in the future. In an attempt to select the most appropriate biomass sources for each specific alkane-based application, a diagram inspired by van Krevelen is applied, taking into account both the C-number and the relative functionality of the product molecules.